Temperature Effect on Corrosion Rate of Metal AA 5052 Using D-Galactose Inhibitors In Sulfuric Acid Media With Electrochemical Method - Arwati, I Gusti Ayu; Syahbana, Fikri; S., Wiwit; Maryani, Yeyen (World Chemical Engineering Journal, 2022)
Aluminum Alloy 5052 (AA 5052) is a metal that can be used as a biopolar plate in proton exchange membrane fuel cell (PEMFC), because it has the advantages of being resistant to corrosion, high conductivity, easy shape and light weight. PEMFC produces electrical energy and the rest of the process in the form of hot water and steam. In a bipolar plate PEMFC environment corrosion can easily occur due to an acidic environment and high operating temperature around 40°C-80°C. For this reason, a treatment is needed to strengthen the corrosion-resistant properties of AA 5052. The coating of the material can be done using the technique of electrophoretic deposition (EPD) using green inhibitor to reduce the corrosion rate. The electrochemical method was carried out to see how much influence temperature had on the corrosion rate of AA 5052. In this study, d-galactose green inhibitor with a concentration of 0.5 g, EPD time of 20 minutes was used, in a PEMFC environmental simulation in 0.5 M H2SO4 sulfuric acid medium, with test temperatures of 25°C (room temperature), 40°C, 60°C, and 80°C. From the results of the analysis using the electrochemical method, there was an effect of temperature on the corrosion rate of AA 5052 without an inhibitor layer of 0.3610 mmpy at room temperature and increased at 80°C 3.9527 mmpy. While AA 5052 which was coated with a d-galactose inhibitor, had a corrosion rate of 0.1678 mmpy at room temperature and continued to increase at a temperature of 80°C 3.7745 mmpy. Inhibitor efficiency was 53.51% at room temperature and decreased with increasing temperature to 4.5% at 80°C.